Social Support and Iron Tablet Supplementation in Adolescents: A Literature Review - Feriyanti, Alma; Putri Rahayu, Agustin (Panakeia Journal of Epidemiology, 2024)
Low adherence to consuming iron supplements among adolescent girls increased their risk of anemia. The prevalence of anemia among adolescents in Indonesia rose from 6.90% to 32.0%. The aim of this study was to examine the relationship between social support and the consumption of iron supplements among adolescent girls in Indonesia. The method used in this article was a literature review, based on articles obtained from the online database Google Scholar. The selected research articles met the inclusion and exclusion criteria established by the authors.The inclusion criteria for the literature review were: a quantitative research approach, full-text availability, study location in Indonesia, and articles published between 2020 and 2024. The exclusion criteria were studies targeting populations other than adolescent girls. A total of 15 articles related to social support and adherence to iron supplementation among adolescents were identified.The results of this review showed that social support including school support, friends, family support, and healthcare worker support was correlated with adherence to iron tablet supplementation among adolescent girls. The conclusion was that social support significantly impacted the improvement of adherence to iron tablet supplementation among adolescent girls.